Students' beliefs about teaching and learning and their perceptions of student-centred learning environments. Issue 5 (3rd September 2018) - Lee, Sang Joon; Branch, Robert Maribe
ABSTRACT: Student-centred learning requires students to be an active participant in knowledge construction. Due to the unique self-directed aspects that characterise student-centred instruction, students may feel uncomfortable and find themselves unprepared for the demands associated with student-centred learning environments (SCLEs). This qualitative case study explored 11 students' beliefs about teaching and learning and how their beliefs influenced their perceptions of a SCLE in a graduate programme. The results showed that students' prior knowledge as well as their beliefs about teaching and learning influenced their perceptions of the SCLE. This study suggests that teachers and educational practitioners acknowledge students' individual differences in their beliefs and prior knowledge, and provide personal support and guidance.